2006
DOI: 10.1590/s1415-43662006000300024
|View full text |Cite
|
Sign up to set email alerts
|

Proposição de valores de referência para a concentração natural de metais pesados em solos brasileiros

Abstract: Para avaliar a extensão da poluição de uma área, é comum se comparar os teores totais de metais pesados encontrados num dado solo com aqueles defrontados em condições naturais (não poluídos) ou com valores de referência (padrões). Propuseram-se através deste estudo: 1) valores de referência (VR) e limites de tolerância (LT) para os mais representativos solos brasileiros, e 2) um modelo para obtenção das concentrações naturais de Cd, Co, Cr, Cu, Ni, Pb e Zn em um solo, a partir dos teores de silte, argila, Mn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
28

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 14 publications
1
9
0
28
Order By: Relevance
“…The RRV were close to the background presented by Fadigas et al (2006). Also, the Latosol samples were undisturbed or nearly undisturbed by human activity.…”
Section: Rrv and Brazilian Backgroundssupporting
confidence: 73%
See 1 more Smart Citation
“…The RRV were close to the background presented by Fadigas et al (2006). Also, the Latosol samples were undisturbed or nearly undisturbed by human activity.…”
Section: Rrv and Brazilian Backgroundssupporting
confidence: 73%
“…The background values and tolerance limits established for the elements Cd, Co, Cr, Cu, Ni, Pb, and Zn, were determined predominantly in samples of distroferric Red Latosol, distroferric Red Nitosol, Brown Latosol and eutroferric Red Argisol (Table 5), herein denominated group G1 (Fadigas et al, 2006). These studies demonstrated that the main physical, chemical and mineralogical characteristics of soils can influence the background values, including clay, Mn, Fe contents and cation exchange capacity (CEC).…”
Section: Rrv and Brazilian Backgroundsmentioning
confidence: 99%
“…However, some heavy metals, like Pb, Hg, As, and Cd, do not have any biological activity and, even at low concentrations, may have a harmful effect on plants (Lasat, 2002). Soils in their natural state have heavy metals at varied concentrations, depending on the material of origin and the processes involved in their formation (Fadigas et al, 2006). There may also be deposition in the soil through industry or use of agricultural inputs such as fertilizers and pesticides (Xue et al, 2003), or diffuse contamination through deposit of aerosols on the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…Nos estudos de Santos-Filho & Rocha (1982) apud Fadigas et al (2002), esses solos apresentam altas concentrações de óxidos de Fe, Mn (manganês) e o Cu. Fadigas et al (2006) propõe valores de referência para a concentração natural de metais em solos brasileiros para serem defrontados com os solos poluídos. Além disso, a existência de um incinerador no Câmpus da UNESP, próximo do ponto P 1 , pode contaminar e liberar material particulado com metais que se deposita rapidamente na superfície do solo e atingir o leito do córrego no período de chuva.…”
Section: Resultsunclassified